Ethical guidelines related to wearable devices: a literature review - Oliveira, Jayne Silva de; Teixeira, João Marcelo Xavier Natário (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
This study presents a literature review of ethical guidelines applicable to wearable devices, whose growing adoption raises important concerns regarding user data privacy and security. These devices, by collecting personal information, may pose privacy risks such as unintentional data sharing or vulnerabilities to data breaches. The study aims to map the main ethical guidelines focused on the security and privacy of wearable device users, analyzing existing solutions and strategies. The review included publications from 2014 to 2024, totaling 16 materials analyzed. The results indicate a variety of proposals, including comprehensive regulations and specific measures such as the implementation of encryption. The combination of these approaches offers greater security and better protection of user privacy.